2014
DOI: 10.2214/ajr.13.10986
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Imaging Utilization: Trends of the Past Decade

Abstract: After decades of continued rise, imaging utilization for inpatients significantly decreased by most measures between FY 2009 and FY 2012. Future studies to evaluate the contribution of various factors to this decline, including efforts to reduce inappropriate use of imaging and concerns about potential harms of radiation exposure, may be helpful in optimizing imaging utilization and resource planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…A number of subsequent publications further increased the evidence and the controversy surrounding this assertion(7,8,21). Although it is possible that concern about ionizing radiation exposure contributed to the decline in use of CT it is unlikely to fully explain the decline, as the use of CT for inpatients at our institution continued to rise till 2009 and, in the current study, the use of non-ionizing MRI also declined after 2008(22). Another potential reason for the decline is the significant recent publicity about the cost of CT and MRI imaging, which may have also contributed to the decrease seen for both of these modalities(23).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…A number of subsequent publications further increased the evidence and the controversy surrounding this assertion(7,8,21). Although it is possible that concern about ionizing radiation exposure contributed to the decline in use of CT it is unlikely to fully explain the decline, as the use of CT for inpatients at our institution continued to rise till 2009 and, in the current study, the use of non-ionizing MRI also declined after 2008(22). Another potential reason for the decline is the significant recent publicity about the cost of CT and MRI imaging, which may have also contributed to the decrease seen for both of these modalities(23).…”
Section: Discussionmentioning
confidence: 59%
“…We limited our study to imaging performed in the ED; some of the decrease might have been due to a deferral of imaging on admitted patients to the inpatient services. However, a study of inpatient imaging use at our institution found a similar decline, making this unlikely (22). In addition, our results are from a single center with over eight years of experience using health IT interventions with CDS targeting inappropriate use of imaging in the ED; it is possible that the implementation of CDS at a new institution might result in less robust initial results.…”
Section: Discussionmentioning
confidence: 88%
“…Imaging CDS and CDS-enabled interventions have been associated with reductions in use of imaging and improved appropriateness (8)(9)(10)(11)(12)(13). Although condition-specific imaging CDS interventions for outpatients (9) and in the emergency department (ED) (10) have been reported, reports on inpatient interventions are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Additionally, the paradigm shift from imaging modalities using high radiation doses to those using minimal or no radiation has also promoted the use of MRI. 3 The increased use of MRI in health care delivery has brought to the fore some major challenges one of which is an increase in the cost of healthcare which includes the cost of purchase and the need to employ skilled personnel like radiographers and radiologists to use the equipment. 4,5 In Ghana, most people pay for this service out of pocket, forcing some clinicians to do a cost-benefit analysis before requesting MRI for their patients.…”
Section: Introductionmentioning
confidence: 99%